Eliminasi Virus pada Bawang Merah dengan Elektroterapi Secara In Vitro - , Retno Pangestuti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
oductivity of shallot is still low i.e. 9.54 t /ha. Low productivity of shallot is affected by low quality of planting materials causedsome factors including the accumulation of virus in planting material due to simultaneous infection on bulb through vegetative propagation. Some researcher were occupied to determine the effect of some major viruses infection to Allium plants and the result showed that the virus infection could reduce yield ranging from 39% to 60%. Therefore, the management production of shallot using virus-free planting materials is very important. The aims of this research were to confirm the visual symptom of virus in shallot plants with suitable method of virus detection and to analyzes virus elimination treatment by electrotherapy and the explant sources on therapy efficiencyof shallot explants. The research was conducted at the Laboratory of Tissue Culture and Virology, Faculty of Agriculture, Gadjah Mada University in November 2011 to August 2012. The experimental design was RCBD factorials with two factors and were replicated in three blocks. The first factor was the explantsourcesi.e. meristem tip (2 mm), basal plate (3-5 mm) and pseudo stem (10-15 mm). The second factor was the electrotherapy currents i.e. 0 mA ,5 mA, 10 mA, and 15 mAwith each treatment in 10 minutes. There were two groups that were plantswith virus infection symptom and plants without symptom treated by the treatments. Shallot varieties used were Super Philips and Ilokos. Virus observation of detection by test plant, DAS ELISA and transmission electron microscopy (TEM). The results showed that plants with specific virus symptom such as mosaic, clorosis, yellow strip and abnormal leaf had positive virus detected by ELISA or TEM. Meristem tip wasthe best explant source in virus elimination both in virus elimination abilities and explant growth after virus elimination treatments. Application of electrotherapy treatment increased the percentage of explants free virus without causing deterioration of explant growth. Combination of meristem tip and electrotherapy 5 mA for 10 minutes treatmentproduced the highesttherapy efficiency i.e. 28.57 %.